2013
DOI: 10.3389/fpsyg.2013.00749
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative meta-analysis of fMRI and PET studies reveals consistent activation in fronto-striatal-parietal regions and cerebellum during antisaccades and prosaccades

Abstract: The antisaccade task is a classic task of oculomotor control that requires participants to inhibit a saccade to a target and instead make a voluntary saccade to the mirror opposite location. By comparison, the prosaccade task requires participants to make a visually-guided saccade to the target. These tasks have been studied extensively using behavioral oculomotor, electrophysiological, and neuroimaging in both non-human primates and humans. In humans, the antisaccade task is under active investigation as a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
98
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 150 publications
(239 reference statements)
16
98
0
1
Order By: Relevance
“…As a neuroimaging tool, 'task-based' functional magnetic resonance imaging (MRI) studies have consistently demonstrated activations in these eye movement-related brain areas (Jamadar et al 2013). Intrinsic functional connectivity (iFC) MRI additionally allows to assess the connectome of distinct brain areas by measuring the similarity of spontaneous low-frequency blood oxygenation level-dependent (BOLD) fluctuations while subjects 'rest' in the scanner without any specific task (Biswal et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As a neuroimaging tool, 'task-based' functional magnetic resonance imaging (MRI) studies have consistently demonstrated activations in these eye movement-related brain areas (Jamadar et al 2013). Intrinsic functional connectivity (iFC) MRI additionally allows to assess the connectome of distinct brain areas by measuring the similarity of spontaneous low-frequency blood oxygenation level-dependent (BOLD) fluctuations while subjects 'rest' in the scanner without any specific task (Biswal et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…6A), which possess a retinotopic map of the contralateral visual field (their location is more inferior than in non‐human primates, in line with similar superior‐toward‐medial‐wall movements of parietal retinotopic areas in humans comparable to LIP). While retinotopy in this region is reported here for the first time, there have been a number of reports of activation in this region associated with visuo‐spatial attention and eye movements [Jamadar et al, 2013; McDowell et al, 2008; Mesulam et al, 2001; O'Reilly et al, 2013; Pierrot‐Deseilligny et al, 2004]. In the reading experiment, all three conditions that involved eye movements—English, Hindi and Dot have significant activation overlapping the anterior cingulate retinotopic region.…”
Section: Resultsmentioning
confidence: 52%
“…Finally, the random color change detection task performed by the subjects during the experiment across all conditions served as a control for endogenous attention. In all three conditions‐ English, Hindi and Dot, significant activation was observed bilaterally near intra parietal/postcentral sulcus, FEF, and dorsomedial frontal eye fields, regions known to be activated by visuo‐spatial attention and eye saccades [Jamadar et al, 2013; McDowell et al, 2008; MĂŒri and Nyffeler, 2008; O'Reilly et al, 2013; Pierrot‐Deseilligny et al, 2004]. The activations in dorsomedial frontal eye fields and parts of parietal cortex are fully attenuated in English vs. Hindi contrast (as well as in Hindi vs.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, KLS patients had significantly lower connectivity between the left dorsal pons and the right frontal eye field, p = 0.041 corrected for multiple comparison at the whole brain level using family wise error (FWE) correction. The peak of the connectivity difference was located at MNI co-ordinates [20, -6, 62], which is adjacent to the peak of antisaccade activation in the frontal eye field identified from a recent meta-analysis (Jamadar et al, 2013). Excluding the unique case of KLS with nystagmus showed similar results but with higher significance, p = 0.027, for the connectivity between the dorsal pons and the frontal eye fields.…”
Section: Resultsmentioning
confidence: 63%
“…The frontal eye field controls eye movements such as saccades and antisaccades (Lynch et al, 2006;Jamadar et al, 2013). There are strong connections between the frontal eye field and the brain stem oculomotor system, including the pontine reticular formation, and the basal ganglia, i.e.…”
Section: Resultsmentioning
confidence: 99%